Nurses' Perceptions on the Overuse of Health Services: A Qualitative Study. Issue 2 (11th January 2018) - Ellen, Moriah E.; Perlman, Saritte
Abstract: Purpose: To examine whether nurses in Israel think there is overuse of health services, the reasons behind the issue, and ways to reduce the overuse. Design: This was a qualitative study using semistructured interviews. A convenience sample of community care nurses from health clinics across Israel was interviewed. Interviews focused on common areas of overuse, outcomes of overuse, causes of overuse, and potential ways to address the issue. Interviews were recorded, transcribed, and analyzed thematically. Findings: Overuse of antibiotics, imaging, blood tests, and prenatal surveillance were cited as main areas of health service overuse. Participants stated that negative outcomes of overuse could be seen at patient, health system, and population levels. Factors influencing overuse included patient satisfaction, physician fears, and insecurities. Potential interventions included improving physicians' diagnostic confidence, increasing appointment times, providing patients with more treatment information, and implementing a unified computerized system across medical institutions. Conclusions: Nurses mentioned physicians and patients as main actors in influencing overuse; hence, those populations should be researched further. The health system was identified as the responsible party to address the issue. Health system leaders must consider potential barriers, and investigate interventions that match current culture and context within the health system. Clinical Relevance: Nurses can play an essential role in limiting overuse and mitigating subsequent harms to patients.